Adjuvant chemotherapy with doxorubicin, ifosfamide, and lenograstim for resected soft-tissue sarcoma (EORTC 62931): a multicentre randomised controlled trial - Woll, Penella J.; Hohenberger, Peter (The lancet. Oncology, 2012)
Summary - Background - The effect of adjuvant chemotherapy on survival for resected soft-tissue sarcoma remains unknown. We investigated the effect of intensive adjuvant chemotherapy on survival in patients after resection of high-risk soft-tissue sarcomas. - Methods - In this multicentre randomised trial, patients with macroscopically resected, Trojani grade II-III soft-tissue sarcomas at any site, no metastases, performance status lower than 2 and aged between 16 and 70 years were eligible within 4 weeks of definitive surgery. Patients were randomly assigned to receive adjuvant chemotherapy or no chemotherapy (control group). Randomisation was done with a minimisation technique, stratified by hospital, site of primary tumour, tumour size, planned radiotherapy, and isolated limb perfusion therapy. Chemotherapy consisted of five cycles of doxorubicin 75 mg/m2, ifosfamide 5 g/m2, and lenograstim every 3 weeks. Patients in both groups received radiotherapy if the resection was marginal or the tumour recurrent. The primary endpoint was overall survival and analyses were done by intention to treat. The final results are presented. This trial is registered with ClinicalTrials.gov, NCT00002641. - Findings - Between February, 1995, and December, 2003, 351 patients were randomly assigned to the adjuvant chemotherapy group (175 patients) or to the control group (176). 258 (73%) of 351 patients received radiotherapy, 129 in each group. Overall survival did not differ significantly between groups (hazard ratio [HR] 0·94 [95% CI 0·68-1·31], p=0·72) nor did relapse-free survival (HR 0·91 [0·67-1·22], p=0·51). 5-year overall survival rate was 66·5% (58·8-73·0) in the chemotherapy group and 67·8% (60·3-74·2) in the control group. Chemotherapy was well tolerated, with 130 (80%) of 163 patients who started it completing all five cycles. 16 (10%) patients had grade 3 or 4 fever or infection, but no deaths due to toxic effects were recorded. - Interpretation - Adjuvant chemotherapy with doxorubicin and ifosfamide in resected soft-tissue sarcoma showed no benefit in relapse-free survival or overall survival. Future studies should focus on patients with larger, grade III, and extremity sarcomas. - Funding - European Organisation for Research and Treatment of Cancer, Rhone-Poulenc-Rorer.